2000
DOI: 10.1001/archotol.126.4.494
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tonsillectomy and Adenoidectomy on Child Behavior

Abstract: This pilot study demonstrates a high prevalence (28%) of abnormal behavior in children undergoing T&A for chronic upper airway obstruction. Scores on a standardized measure of behavior improve following T&A, but larger studies with increased statistical power are needed to clarify the degree of improvement and its clinical importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
114
1
8

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(129 citation statements)
references
References 23 publications
(32 reference statements)
6
114
1
8
Order By: Relevance
“…In a study involving 36 children, Goldstein et al showed a prevalence of 28% of emotional and behavioral problems 18 , and this is in agreement with the findings of the present study. The limitations of this study include small samples and a lack of a healthy children control group.…”
Section: Discussionsupporting
confidence: 93%
“…In a study involving 36 children, Goldstein et al showed a prevalence of 28% of emotional and behavioral problems 18 , and this is in agreement with the findings of the present study. The limitations of this study include small samples and a lack of a healthy children control group.…”
Section: Discussionsupporting
confidence: 93%
“…Goldstein et al 55 IV 450 All showed behavior improvement except Davis et al 49 Goldstein et al 243 Long-term behavior improvement in Mitchell et al 53 Hogan et al 48 Li et al 238 Roemmich et al 191 Tran et al 58 Wei et al 245 Mitchell et al 53 Davis et al 49 Aggression, oppositional, and social problems 54 Long-term improvements ≥1 y 52 , 53 Goldstein et al 55 Sohn et al 56 Silva and Leite 57 Tran et al 58 Chervin et al 37 I 105 Long-term improvements at 1 y Sleep quality Constantin et al 54 IV 590 Improved in both studies Wei et al 245 …”
Section: Areas For Future Researchmentioning
confidence: 99%
“…There were 9 recent level III or IV studies, most of which showed a correlation between the presence/ 40 Galland et al 237 Golan et al 239 Gottlieb et al 213 Johnson and Roth 45 LeBourgeois et al 230 Mitchell and Kelly 240 Owens et al 189 Roemmich et al 191 Urschitz et al 229 Montgomery 240 Mitchell and Kelly 241 Rudnick and Mitchell 242 Suratt et al 43 III 114 O'Brien et al 24 I 118 Behavior problems, general Goldstein et al 55 IV 1946 Behavior generally measured by using parent questionnaire Goldstein et al 243 Hogan et al 48 Li et al 238 Mitchell and Kelly 241 Mulvaney et al 32 Owens et al 189 Roemmich et al 191 Rosen et al 244 Rudnick and Mitchell 242 Tran et al 58 Wei et al 245 Aggression, oppositional and social problems…”
Section: Cardiovascular Effects Of Osasmentioning
confidence: 99%
“…However, it is well documented that as many as 80% of children have polysomnographically determined improved breathing during sleep and resolution of SRBD after A/T (25,26), and our results would suggest from subjective measures that up to 60% improved depending on the breathing item chosen. Others have also shown significant improvements of many polysomnographic-derived variables (6,27,28). A recent study evaluating polysomnographic data before and a few months after surgery showed significant improvements in all respiratory parameters with a greater improvement in the respiratory disturbance index in non-REM compared with REM sleep and significant improvements in the arousal index (29).…”
mentioning
confidence: 97%